Aplikasi Pencatatan Keuangan Berbasis Android Pada CV Fortuna Aiko Karanganyar - Aji, Cevin Kuncoro; Widyaningsih, Pipin; Sundari, Sundari (Politeknik Indonusa Surakarta, 2023)
Financial records for an organization is a sensitive and important activity. Making financial records has its own standards so it cannot be done arbitrarily. CV. Fortuna Aiko Karanganyar records daily financial transactions using books and Microsoft Excel. The recording process is carried out twice, namely in the book and in the Excel application for the purpose of making reports. This financial recording model is still ineffective and does not meet organizational needs regarding the preparation of financial reports in real time. The research aims to create an application for recording financial transactions that can be accessed easily by owners and admins. The system development method used is waterfall. The system analysis method uses the PIECES framework. System modeling uses UML. Testing the system using black box testing. The result of the research is the financial recording application that is used to help CV. Fortuna Aiko to manage daily financial transactions. Application features consist of managing account data, managing business data, making journals, ledgers, income statements and balance sheets which can be accessed via Android-based smart phone devices. The results of functionality testing show that the application can function according to its functionality to manage financial transactions.